Jenis-jenis Gulma yang Ditemukan di Perkebunan Kelapa Sawit PT. Incasi Raya Pangian sebagai Buku Ilmiah Populer - Karina, Karina; Nursyahra, Nursyahra; Sari, Liza Yulia (Biocaster : Jurnal Kajian Biologi, 2025)
PT. Incasi Raya Pangian is a company engaged in oil palm plantations with a land area of 6,890 hectares, located in Nagari Sinamar, Asam Jujuhan District, Dharmasraya Regency, West Sumatra Province. One of the main problems in oil palm cultivation is the presence of weeds that can reduce productivity by up to 20% through competition in the absorption of water, light, and nutrients. This research aims to identify the types of weeds that grow in oil palm plantations and compile them in the form of popular scientific books as an educational medium for the community and educators. The research was carried out in two stages. The first stage was carried out to obtain research weed data using the 10-meter transect method with five plots measuring 1 m x 1 m which were arranged alternately in the plantation area of PT. Incasi Raya Pangian, Nagari Sinamar, Dharmasraya Regency. The second stage is the preparation of popular scientific books, where weed samples are collected, preserved, and identified using botanical literature at the Botanical Laboratory of the University of PGRI West Sumatra. The results showed that there were 33 species of weeds from 27 families, consisting of 28 species of the Spermatophyta Division and 5 species of the Pteridophyta Division. Some common species include Ageratum conyzoides, Clidemia hirta, and Cyperus rotundus. The popular scientific books produced have the potential to be a source of practical information for the community, as well as support sustainable weed management in oil palm plantations.